The Role of Critical Reading to Promote Students’ Critical Thinking and Reading Comprehension - Syaadiah Arifin (Universitas Pendidikan Ganesha, 2020)
Developing students' critical thinking and reading comprehension is crucial, particularly for those in colleges, because they need to read numerous scientific journals and textbooks written in English. Therefore, students need to employ critical reading strategies to raise their critical thinking skills for a successful academic life. However, current studies have shown a lack of critical thinking strategies among Indonesian students, thereby leading to various academic problems, particularly the inability to comprehend English. Therefore, this research aims to explore critical reading's role to support students' critical thinking and reading comprehension skills when reading a text. This is a qualitative research with the purposive random technique used to obtain data from seven (7) EFL non–English major undergraduate students in their 2nd semester through three (3) short argumentative texts, a semi-structured interview, and students' answers in written forms. The results showed that students developed their critical thinking skills and improved their reading comprehension in varying degrees by exposure to numerous tasks.